Child cancer counselling network evaluation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology, Massey University, New Zealand. EMBARGOED indefinitely. - Murray, Houston Brooke (Massey University, 2023)
The existing literature surrounding childhood cancer and the psychological implications for the patient and their family, has provided strong evidence that there is a need for psychological support to the whole family unit through a child’s cancer journey. The Child Cancer Counselling Network (CCCN) was established in Aotearoa New Zealand to connect families in need with mental health providers around the country, either online or in person. The overall aim of this research was to evaluate the network from the perspective of the clinicians, which has not been done before. The research question is: “How do clinicians experience the Child Cancer Counselling Network?”. The objectives were to understand the value of the network from the perspective of the clinicians, get rich detailed information from clinicians who work for CCCN about their reasons for being involved, their backgrounds, and experience as a clinician and evaluate the CCCN looking at the clinicians perceptions of training, administration, interventions, and overall value of the programme. Research was conducted through the interview and analysis processes of the qualitative research method, Interpretative Phenomenological Analysis (IPA) to provide the deep and rich lived experiences of the CCCN clinicians. Three core themes and additional subthemes were discovered. Core theme one is the clinicians reasons for being involved in the network through their heart reasons, lived experiences and self-care practices. Core theme two is the significant value of the network from the clinicians perspective, telehealth, and clients they saw. Core theme three is the procedures of the network with its unique training, stages which the services are used and clinician type. These core themes and sub-themes helped to achieve the research objectives of understand the value of the network from the perspective of the clinicians, gaining rich detailed information from clinicians who work for CCCN about their reasons for being involved, their backgrounds, and experience as a clinician and evaluating the CCCN looking at the clinicians perceptions of training, administration, interventions, and overall value of the programme. A child cancer journey is an extraordinarily challenging situation and the ability for these talented and passionate clinicians to assist in making this journey easier to navigate is vital in Aotearoa New Zealand.
Embargoed indefinitely.
Keywords: 520303 Counselling psychology